Nursing Students’ Knowledge About Autism Among Children: A Cross-Sectional Study: Pengetahuan Mahasiswa Keperawatan Tentang Autisme Pada Anak: Sebuah Studi Cross-Sectional - Awad, Kadhim Jawad (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Based on their experience providing healthcare to children with autism, nursing professionals should be able to comprehend and offer therapeutic support to autistic children because they have a unique perspective on the world. Objectives: to evaluate nursing students' understanding of childhood autism. Methods: From October 18, 2023, until March 25, 2024, University of Basrah nursing students participated in this study. One hundred undergraduate students from the University of Basrah's College of Nursing make up the study sample. They were selected at random. There are sixty females and forty males. A questionnaire with thirty questions regarding autism served as the study's tool to gauge students' understanding of the condition. The statistical tool for social sciences, SPSS version 20, was used to examine the data, which is presented as frequency and percentage. The correlation was evaluated using the mean score and significance. among the various variables. Results: About (100) students participated in this study, and the most frequent The age group was from 21 to 23 years (48%), and this sample consisted of (40) male and (60) female students. (83) of the sample members were single. These results. This is consistent with the findings that most students (63%) have good knowledge About autism, (30%) of them have moderate knowledge, and (6%) of them have Weak knowledge. Conclusion: Most of the pupils were between the ages of 21 and 23. There are more females than males in the population. As a group of individuals situated between the general public and medical experts, nursing students may be thought of as having a quite high level of autism awareness. Highlights: Nursing students must understand autism for effective therapeutic support. Random sample of 100 students; data analyzed using SPSS. Majority aged 21–23; 63% demonstrated good autism knowledge. Keywords: Nursing Students, Knowledge, Autism, Children.